Necessary condition analysis for sustainable channel governance in fast-moving markets - Santos-Jaén, José Manuel; Pemartín, María; Gimeno-Arias, Fernando; León-Gómez, Ana María (Emerald, 2025)
The purpose of this paper is to analyse marketing channel governance through the most relevant elements of the relationship (commitment, trust, dependence and enforcement) in light of a new analytical method – necessary condition analysis (NCA) – that brings fresh perspectives to previous studies. The overlooked fast-moving consumer goods (FMCG) sector is chosen to test the proposed model because its high product turnover and changing consumer demands make effective management and close collaboration between trading partners even more necessary than in other sectors. Based on a sample of 204 Spanish distributors – both wholesalers and retailers – in the FMCG sector distribution channel who were contacted through LinkedIn, a governance model in the distribution channel is established and validated via structural model analysis using PLS-SEM, NCA and predictive performance analysis. The results provide empirical support for the proposed model from the perspective of probability, establishing an efficient distribution channel governance formula in FMCG. However, analysis of the proposed relationships in terms of necessity reveals that a high level of social and contractual enforcement cannot be achieved without a certain level of trust and commitment between partners, but that it can be achieved without any dependence. The study highlights that fostering trust and commitment is essential for governance in FMCG distribution channels, as dependence alone is not a necessary condition for achieving strong contractual and social enforcement. Managers should focus on long-term relationship building rather than short-term transactional gains to enhance channel performance. Given the competitive nature of the FMCG sector and the increasing power of retailers, companies can improve governance effectiveness by investing in relational mechanisms that strengthen collaboration with their partners.
https://openpolicyfinder.jisc.ac.uk/id/publication/2818
Keywords: Canales de distribución (Comercio); Consumo - Modelos econométricos; Relationship; Enforcement; Marketing channel; FMCG; PLS-SEM; Necessary condition analysis (NCA)